Preparation method and application of skin-friendly matt finish non-slip flexible silica gel
By introducing phosphorus silicon flame retardant and alkaline magnesium sulfate crystals into silicone rubber, the problem of insufficient mechanical properties and hydrophilic and skin-friendly properties of traditional silicone rubber materials is solved, and better flame retardant and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411837317.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional silicone rubber materials have disadvantages such as poor mechanical properties and poor surface hydrophilicity, which limits their practical application in electronics and electrical appliances, daily necessities and other fields.
Polymerization of pentaerythritol diphosphate diphosphate chloride and bis(salicylene methyl ester Schiff base) diphenylsiloxane monomer, and hydrolyzed by sodium hydroxide, a phosphorus silicon flame retardant containing sodium carboxylate group was obtained, and mixed and vulcanized with alkaline magnesium sulfate crystal, methyl vinyl silicone rubber, white carbon black, etc., to prepare skin-friendly and matte surface anti-smooth flexible silicone.
The surface hydrophilic and skin-friendly properties of silicone materials are improved, while the flame retardant and mechanical properties are enhanced, the tensile strength and elongation at break are significantly improved, and the ultimate oxygen index and vertical combustion grade are improved.
Smart Images

Figure CN119662027A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone rubber, and in particular to a preparation method and application of skin-friendly matte non-slip flexible silicone. Background Art
[0002] Silicone rubber has good elasticity, temperature resistance, aging resistance and other properties, and is widely used in electronic and electrical fields such as corrosion-resistant parts, daily necessities such as silicone pillows and mattresses, and women's products such as bras and nipple covers. Traditional silicone rubber has disadvantages such as poor mechanical properties and poor surface hydrophilicity and skin affinity, which limits the practical application of silicone rubber materials.
[0003] Basic magnesium sulfate crystal is a new type of inorganic fiber material, which has a good application in polymer materials such as plastics and rubbers. It can be used as a reinforcing agent, flame retardant, matte agent, etc. to improve the mechanical strength and flame retardant properties of the material. Patent CN109370117B discloses a highly flame-retardant and aging-resistant fluororubber cable sheath material, which uses fluororubber, acrylate rubber, EPDM rubber, benzyl triphenylphosphine chloride, white carbon black, basic magnesium sulfate whisker, etc. as raw materials. The obtained cable sheath material has good flame retardant properties, heat resistance and aging resistance. However, the patent does not improve the hydrophilic and skin-friendly properties of the rubber material. Summary of the invention
[0004] (I) Technical problems to be solved: The present invention provides a method for preparing a skin-friendly matte non-slip flexible silicone with high flame retardancy and good hydrophilicity.
[0005] (II) Technical solution: A method for preparing a skin-friendly matte non-slip flexible silicone comprises the following steps:
[0006] Step S1, add acetonitrile and pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 80-85°C, stir, dropwise add triethylamine and acetonitrile solution containing bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer, carry out polymerization reaction for 8-12h, filter after cooling, wash with acetonitrile and water in turn, add the product to methanol, add 120-140g / L sodium hydroxide aqueous solution, heat to 80-90°C, hydrolyze for 6-8h, filter after cooling, wash with water, and dry to obtain a phosphorus silicon flame retardant.
[0007] Step S2, adding methyl vinyl silicone rubber, phosphorus silicon flame retardant, and basic magnesium sulfate crystals into an open mill for mixing, then adding white carbon black, continuing to mix, and finally adding dipentadienyl vulcanizing agent, vulcanizing in a flat vulcanizer, cooling and discharging, to obtain skin-friendly matte non-slip flexible silicone.
[0008] Preferably, in step S1, the molar ratio of pentaerythritol diphosphate diphosphoryl chloride (CAS No. 714-87-4), triethylamine, and bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer is 1:(1.8-2.2):(1-1.1).
[0009] Preferably, the preparation method of the bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer comprises the following steps: adding ethanol, bis(4-aminophenoxy)dimethylsilane (CAS No. 1223-16-1) and methyl 5-formylsalicylate (CAS No. 41489-76-3) in a molar ratio of 1:(2-2.1) into a flask, dropping glacial acetic acid, heating to 75-80°C, reacting for 5-8h, filtering after cooling, washing with water, and recrystallizing the product in acetonitrile to obtain the bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer.
[0010] Preferably, in step S2, the mass ratio of methyl vinyl silicone rubber, phosphorus silicon flame retardant, basic magnesium sulfate crystal, white carbon black, and dipentadienyl vulcanizing agent is 100:(15-30):(3-10):(10-20):(0.8-1.3).
[0011] Preferably, in step S2, the vulcanization temperature is 170-180° C. and the time is 10-20 min.
[0012] (III) Technical effect of the present invention: The present invention utilizes pentaerythritol diphosphate diphosphoryl chloride and bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer for polymerization reaction, and then hydrolyzes it with sodium hydroxide to obtain a phosphosilicate flame retardant containing a sodium carboxylate group, and then mixes it with basic magnesium sulfate crystals, methyl vinyl silicone rubber, white carbon black, etc., and vulcanizes it to obtain a skin-friendly matte non-slip flexible silicone.
[0013] The phosphorus silicon flame retardant of the present invention contains a siloxane structural unit similar to methyl vinyl silicone rubber, so that the flame retardant has good compatibility with silicone rubber and will not affect the mechanical properties of silicone materials. In addition, the phosphorus silicon flame retardant contains a large number of hydrophilic sodium carboxylate groups, which can increase the surface water contact angle of the silicone material and improve the surface hydrophilicity and skin-friendly properties of the silicone material. At the same time, the phosphorus silicon flame retardant contains spirocyclic phosphate and siloxane structures to form a phosphorus silicon flame retardant system, thereby improving the flame retardant properties of the silicone material.
[0014] The phosphorus silicon flame retardant of the present invention contains a sodium carboxylate group, which can interact with the surface of the basic magnesium sulfate crystal, so that the phosphorus silicon flame retardant is coated on the surface of the basic magnesium sulfate crystal. Since the phosphorus silicon flame retardant and the methyl vinyl silicone rubber have good compatibility, the basic magnesium sulfate crystal can be evenly dispersed in the silica gel material matrix, which plays a better reinforcing role and significantly improves the tensile strength and elongation at break of the silica gel material. In addition, the basic magnesium sulfate crystal and the phosphorus silicon flame retardant play a synergistic flame retardant role, further improving the limiting oxygen index and vertical combustion grade of the silica gel material, and showing better flame retardant performance.
[0015] The basic magnesium sulfate crystals of the present invention can also play the role of a matte agent and an anti-slip agent. The basic magnesium sulfate crystals are uniformly generated in the silica gel material matrix, and form a fine concave-convex structure on the surface, which can produce a strong light diffuse reflection effect and has a good extinction effect, which is beneficial to reducing the glossiness of the silica gel surface, so that the silica gel presents a matte effect, and the fine concave-convex structure formed on the silica gel surface is beneficial to increasing the contact area and friction, and improving the anti-skid and anti-slip performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is the reaction formula for preparing bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer.
[0017] Figure 2 This is the reaction formula for preparing phosphorus silicon flame retardant. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0019] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0020] Methyl vinyl silicone rubber, Anhui Iyota Silicone Oil Co., Ltd. White carbon black, average particle size 3000 mesh, Guangzhou Yinuo Chemical Technology Co., Ltd.
[0021] Basic magnesium sulfate whiskers were prepared according to the method of the journal "Chemical Industry Journal", Volume 72, Issue 6, 2021, "Controllable Preparation of Basic Magnesium Sulfate Whiskers and the Influence Mechanism of Different Ions".
[0022] Embodiment 1:
[0023] (1) Add 400 mL of ethanol, 40 mmol of bis(4-aminophenoxy)dimethylsilane, and 80 mmol of methyl 5-formylsalicylate into a flask, add 6 mL of glacial acetic acid dropwise, heat to 80° C., condense and reflux for 5 h, cool and filter, wash with water, and recrystallize the product in acetonitrile to obtain a bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer.
[0024] (2) Add 200 mL of acetonitrile and 50 mmol of pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 85° C., stir, dropwise add 100 mmol of triethylamine and 250 mL of an acetonitrile solution containing 50 mmol of bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer, condense and reflux to carry out polymerization reaction for 8 h, cool and filter, wash with acetonitrile and water in turn, add the product to 500 mL of methanol, add 400 mL of 130 g / L sodium hydroxide aqueous solution, heat to 85° C., hydrolyze for 8 h, cool and filter, wash with water, and dry to obtain a phosphorus silicon flame retardant.
[0025] (3) 1000 g of methyl vinyl silicone rubber, 150 g of phosphorus silicon flame retardant, and 30 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 200 g of white carbon black was added and the mixing was continued. Finally, 10 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0026] Embodiment 2:
[0027] (1) Add 400 mL of ethanol, 40 mmol of bis(4-aminophenoxy)dimethylsilane, and 84 mmol of methyl 5-formylsalicylate into a flask, add 5 mL of glacial acetic acid dropwise, heat to 75° C., condense and reflux for 8 h, cool and filter, wash with water, and recrystallize the product in acetonitrile to obtain a bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer.
[0028] (2) Add 250 mL of acetonitrile and 50 mmol of pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 80° C., stir and dropwise add 90 mmol of triethylamine and 250 mL of an acetonitrile solution containing 55 mmol of bis(salicylicaldehyde methyl ester Schiff base) diphenylsiloxane monomer, condense and reflux to carry out polymerization reaction for 12 h, cool and filter, wash with acetonitrile and water in turn, add the product to 500 mL of methanol, add 500 mL of 120 g / L sodium hydroxide aqueous solution, heat to 80° C., hydrolyze for 8 h, cool and filter, wash with water, and dry to obtain a phosphorus silicon flame retardant.
[0029] (3) 1000 g of methyl vinyl silicone rubber, 200 g of phosphorus silicon flame retardant, and 50 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 150 g of white carbon black was added and the mixing was continued. Finally, 13 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 175° C. for 20 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0030] Embodiment 3:
[0031] (1) Add 250 mL of acetonitrile and 50 mmol of pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 80° C., stir, dropwise add 110 mmol of triethylamine and 250 mL of an acetonitrile solution containing 50 mmol of bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer (prepared in the same manner as in Example 1), condense and reflux to carry out polymerization reaction for 12 h, cool and filter, wash with acetonitrile and water in turn, add the product to 400 mL of methanol, add 400 mL of a 140 g / L sodium hydroxide aqueous solution, heat to 85° C., hydrolyze for 8 h, cool and filter, wash with water, and dry to obtain a phosphorus silicon flame retardant.
[0032] (2) 1000 g of methyl vinyl silicone rubber, 250 g of phosphorus silicon flame retardant, and 70 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 150 g of white carbon black was added and the mixing was continued. Finally, 8 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 180° C. for 20 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0033] Embodiment 4:
[0034] (1) Add 200 mL of acetonitrile and 50 mmol of pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 80° C., stir, dropwise add 100 mmol of triethylamine and 300 mL of an acetonitrile solution containing 55 mmol of bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer (prepared in the same manner as in Example 1), condense and reflux for polymerization for 8 h, cool and filter, wash with acetonitrile and water in turn, add the product to 500 mL of methanol, add 400 mL of a 120 g / L sodium hydroxide aqueous solution, heat to 90° C., hydrolyze for 6 h, cool and filter, wash with water, and dry to obtain a phosphorus silicon flame retardant.
[0035] (2) 1000 g of methyl vinyl silicone rubber, 300 g of phosphorus silicon flame retardant, and 100 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 100 g of white carbon black was added and the mixing was continued. Finally, 12 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0036] Comparative Example 1:
[0037] (1) 1000 g of methyl vinyl silicone rubber and 200 g of white carbon black were added to an open mill for mixing, and then 10 g of a dipentadienyl vulcanizing agent was added. The mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer, and the material was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0038] Comparative Example 2:
[0039] (1) 1000 g of methyl vinyl silicone rubber and 150 g of phosphorus silicon flame retardant (prepared in the same manner as in Example 1) were added to an open mill for mixing, and then 200 g of white carbon black was added and the mixing was continued. Finally, 10 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0040] Comparative Example 3:
[0041] (1) 1000 g of methyl vinyl silicone rubber and 30 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 200 g of white carbon black was added and the mixing was continued. Finally, 10 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0042] Comparative Example 4:
[0043] (1) Add 200 mL of acetonitrile and 50 mmol of pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 85° C., stir, dropwise add 100 mmol of triethylamine and 250 mL of an acetonitrile solution containing 50 mmol of bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer (prepared in the same manner as in Example 1), condense and reflux to carry out polymerization reaction for 8 h, cool and filter, wash with acetonitrile and water in turn, and dry to obtain a phosphorus silicon flame retardant.
[0044] (2) 1000 g of methyl vinyl silicone rubber, 150 g of phosphorus silicon flame retardant, and 30 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 200 g of white carbon black was added and the mixing was continued. Finally, 10 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0045] Comparative Example 5:
[0046] (1) Add 200 mL of acetonitrile and 50 mmol of pentaerythritol diphosphate diphosphoryl chloride into a flask, heat to 85° C., stir, dropwise add 100 mmol of triethylamine and 250 mL of an acetonitrile solution containing 50 mmol of hydroquinone, condense and reflux to carry out polymerization reaction for 8 h, cool and filter, wash with acetonitrile and water in turn, and dry to obtain a phosphorus-containing flame retardant.
[0047] (2) 1000 g of methyl vinyl silicone rubber, 150 g of phosphorus-containing flame retardant, and 30 g of basic magnesium sulfate crystals were added to an open mill for mixing, and then 200 g of white carbon black was added and the mixing was continued. Finally, 10 g of dipentadienyl vulcanizing agent was added and the mixture was vulcanized at 170° C. for 30 min in a flat vulcanizer. The mixture was cooled and discharged to obtain a skin-friendly matte non-slip flexible silicone.
[0048] The water contact angle on the silica gel surface was tested by static contact angle measurement using an optical contact lens tester.
[0049] The tensile properties of silicone are tested according to GB / T 528-2008 standard.
[0050] The flame retardant properties of silicone are tested according to GB / T 10707-2008 standard.
[0051] Table 1
[0052]
[0053] As can be seen from Table 1, the water contact angle of the silicone material of Comparative Example 1 is large, the surface hydrophilicity is poor, and the tensile strength and elongation at break are small, the mechanical properties are poor, and the limiting oxygen index is low, there is no grade for vertical combustion, and the flame retardancy is poor.
[0054] Comparative Example 2 adds a phosphosilicate flame retardant, which contains a siloxane structural unit similar to methyl vinyl silicone rubber, so that the flame retardant has good compatibility with silicone rubber. When added to the silicone matrix, it has little effect on the mechanical properties of the silicone material, and still has good tensile strength and elongation at break. The phosphosilicate flame retardant contains a large number of hydrophilic sodium carboxylate groups, which can increase the surface water contact angle of the silicone material, improve the surface hydrophilicity and skin-friendly properties of the silicone material, and the phosphosilicate flame retardant contains spirocyclic phosphate and siloxane structures to form a phosphosilicate flame retardant system, which improves the flame retardant properties of the silicone material, increases the limiting oxygen index, and the vertical combustion level reaches V-1 level.
[0055] In Comparative Example 3, basic magnesium sulfate crystals were added, which had poor compatibility with methyl vinyl silicone rubber and were difficult to be evenly dispersed in the silicone material matrix. The reinforcing effect was not obvious and the tensile strength and elongation at break of the silicone material could not be well enhanced.
[0056] In Example 1-4, phosphorus silicon flame retardant and basic magnesium sulfate crystals are added. During the mixing process, the sodium carboxylate group contained in the phosphorus silicon flame retardant can interact with the surface of the basic magnesium sulfate crystals, so that the phosphorus silicon flame retardant is coated on the surface of the basic magnesium sulfate crystals. Since the phosphorus silicon flame retardant and methyl vinyl silicone rubber have good compatibility, the basic magnesium sulfate crystals can be evenly dispersed in the silica gel material matrix, so that the basic magnesium sulfate crystals play a good reinforcing role, and significantly improve the tensile strength and elongation at break of the silica gel material. At the same time, the phosphorus silicon flame retardant reduces the surface water contact angle of the silica gel material, plays a synergistic flame retardant role with the basic magnesium sulfate crystals, improves the limiting oxygen index and vertical combustion grade of the silica gel material, and shows better hydrophilic and skin-friendly properties and flame retardant properties.
[0057] The ester group of the phosphosilicate flame retardant of Comparative Example 4 has not been hydrolyzed by sodium hydroxide and does not contain a sodium carboxylate group, so it cannot improve the hydrophilicity of the silica gel material, and cannot interact with the surface of the basic magnesium sulfate crystals, making it difficult to effectively coat the surface of the basic magnesium sulfate crystals. This results in poor dispersibility of the basic magnesium sulfate crystals in the silica gel material, poor reinforcement effect, and low tensile strength and elongation at break.
[0058] Comparative Example 5 uses pentaerythritol diphosphate diphosphoryl chloride and hydroquinone for polymerization reaction, and the obtained phosphorus-containing flame retardant does not contain siloxane structural units, has poor compatibility with methyl vinyl silicone rubber, has a great influence on the mechanical properties of silicone materials, and significantly reduces the tensile strength and elongation at break.
Claims
1. A method for preparing a skin-friendly matte non-slip flexible silica gel, characterized in that: The preparation method comprises the following steps: Step S1, adding acetonitrile and pentaerythritol diphosphate diphosphoryl chloride into a flask, heating to the reaction temperature, adding triethylamine and an acetonitrile solution containing bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer dropwise after stirring, carrying out polymerization reaction, filtering and washing after cooling, adding the product into methanol, adding sodium hydroxide aqueous solution, carrying out hydrolysis, filtering, washing and drying after cooling, and obtaining a phosphorus silicon flame retardant; Step S2, adding methyl vinyl silicone rubber, phosphorus silicon flame retardant, and basic magnesium sulfate crystals into an open mill for mixing, then adding white carbon black, continuing to mix, and finally adding dipentadienyl vulcanizing agent, vulcanizing in a flat vulcanizer, cooling and discharging, to obtain skin-friendly matte non-slip flexible silicone.
2. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 1, characterized in that: In the step S1, the reaction temperature is 80-85°C, the polymerization reaction time is 8-12 hours; the hydrolysis reaction temperature is 80-90°C, and the time is 6-8 hours.
3. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 1, characterized in that: In step S1, the mass concentration of the sodium hydroxide aqueous solution is 120-140 g / L.
4. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 1, characterized in that: In the step S1, the molar ratio of pentaerythritol diphosphate diphosphoryl chloride, triethylamine, and bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer is 1:(1.8-2.2):(1-1.1).
5. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 4, characterized in that: The preparation method of the bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer comprises the following steps: adding ethanol, bis(4-aminophenoxy)dimethylsilane and methyl 5-formyl salicylate into a flask, dropping glacial acetic acid, heating to 75-80°C, reacting for 5-8h, filtering after cooling, washing with water, and recrystallizing the product in acetonitrile to obtain the bis(salicylaldehyde methyl ester Schiff base) diphenylsiloxane monomer.
6. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 5, characterized in that: The molar ratio of the bis(4-aminophenoxy)dimethylsilane to methyl 5-formylsalicylate is 1:(2-2.1).
7. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 1, characterized in that: In step S2, the mass ratio of methyl vinyl silicone rubber, phosphorus silicon flame retardant, basic magnesium sulfate crystal, white carbon black, and dipentadienyl vulcanizing agent is 100:(15-30):(3-10):(10-20):(0.8-1.3).
8. The method for preparing the skin-friendly matte non-slip flexible silica gel according to claim 1, characterized in that: In step S2, the vulcanization temperature is 170-180° C. and the time is 10-20 minutes.
Citation Information
Patent Citations
A high flame-retardant and aging-resistant fluororubber cable sheath material
CN109370117B
Method for synthesizing nucleoside triphosphate and nucleoside diphosphate from all-protected nucleoside phosphoramidite intermediate through acid catalysis
CN103193843A
Polyvinyl chloride elastomer cable material for charging pile cables and preparation method thereof
CN107266829A
Diacid monomer, copolymerized flame retardant, copolymerized flame-retardant nylon and preparation methods thereof
CN113801162A
Flame-retardant silicone rubber material as well as preparation method and application thereof
CN117866443A